2014
DOI: 10.1177/1078345813505445
|View full text |Cite
|
Sign up to set email alerts
|

Continued Detention Involvement and Adolescent Marijuana Use Trajectories

Abstract: Justice-involved youth have high rates of marijuana use. Less is known about what may drive these rates, particularly when justice-involved youth return to the community. One factor that has been implicated is continued detention involvement. Yet, it is unknown how this factor may influence marijuana use trajectories. Using longitudinal growth curve modeling, the researchers evaluated the association between continued detention involvement and marijuana use trajectories in two large, ethnically diverse samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
(85 reference statements)
1
2
0
Order By: Relevance
“…Congruent with prior work (Feldstein Ewing, Schmiege, et al, 2014), we also found that youth who spent more time in a facility or other supervised setting showed less marijuana and heavy alcohol use. While supervised settings do not always ensure treatment or rehabilitation, the findings here suggest the value of continuing to examine the connection between time off of the street and in protective settings for this population and decreasing rates of use.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…Congruent with prior work (Feldstein Ewing, Schmiege, et al, 2014), we also found that youth who spent more time in a facility or other supervised setting showed less marijuana and heavy alcohol use. While supervised settings do not always ensure treatment or rehabilitation, the findings here suggest the value of continuing to examine the connection between time off of the street and in protective settings for this population and decreasing rates of use.…”
Section: Discussionsupporting
confidence: 44%
“…To that end, studies have supported the relevance of demographic factors in high-risk youths’ progression of alcohol and marijuana use over time (e.g., race/ethnicity; socioeconomic status; family factors; time in monitored settings) (e.g., Feldstein Ewing, Schmiege, & Bryan, 2014; Haberstick et al, 2014; Prado et al, 2012). Whereas others have shown the contribution of personality-level factors in youth substance use rates over time (e.g., externalizing disorders, impulsivity) (e.g., Abram et al, 2015; Mauricio et al, 2009; Prince van Leeuwen, Creemers, Verhulst, Ormel, & Huizink, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation